Digitization, restoration and visualization of terracotta figurines from the 'House of Orpheus', Nea Paphos, Cyprus - Papantoniou, G.; Lanitis, Andreas; Loizides, Fernando (My University, 2012)
The terracotta figurines from the so-called ‘House of Orpheus’ in Nea Paphos,Cyprus, and in particular the terracotta figurines excavated between 1982-1992, form part of a significant material assemblage that spans in time from Hellenistic to Roman times. These high quality terracotta figurines fall within the mainstream of Cypriot art and its associated ancient technological and cultural systems. The research project presented here, aims at a systematic assessment of this assemblage employing stylistic, analytical, computational and theoretical methods of study. Emphasis is given to the digitization process that involves 3D scanning of items of interest; and the subsequent processing that aims to reconstruct and visualize specific fragmented specimens in their anticipated full shape and colour. Also presented are our plans for developing interactive applications that utilize 3D models of the specimens.
Keywords: Terracotta figurines, Ancient--Cyprus; Visualization